Molecular screening of parvovirus in the Rattus sp. - Nur Anis Aryani Zakaria (2020)
Parvovirus is recognised as small as 18-26 nm in size, single-stranded DNA and non-enveloped virus. It is stable in extreme environment and resistant to inactivation by heat, acid, solvents or disinfectants. Parvovirus that is known to infect Rattus sp. include Kilham rat virus and Toolan's H-I virus, that oftenly induce lesions to the liver, central nervous system, lymphoid system, and other tissues. Rats abundant in urban environments become major pests of public health significance that potentially transmit diseases. Information regarding the parvovirus detection in Rattus sp. is very limited and no data reported in Malaysia.Therefore, this study aimed to determine the status of
parvovirus screening among the Rattus sp. in Klang Valley. A total of twenty-three (n=23) rats' archived serum samples was subjected to polymerase chain reaction (PCR) assay targeting the parvovirus non-structural (NS) protein. Our results showed none of the samples were positive for parvovirus. The non-viraemic state of the infection might contribute to the condition or the rat might not be exposed to the infection yet. In conclusion, this study revealed that the Rattus sp. in Klang Valley area are less likely to be infected by parvovirus.
Project paper (D.V.M) - Universiti Putra Malaysia, 2020.